Metabolic reprogramming induced by DCA enhances cisplatin sensitivity through increasing mitochondrial oxidative stress in cholangiocarcinoma - Qin, Hanjiao; Zheng, Ge; Li, Qiao; Shen, Luyan (Frontiers in Pharmacology, 2023)
Cholangiocarcinoma is one of the most common malignancies of the hepatobiliary system. Many studies have indicated that cholangiocarcinoma has obvious primary multidrug resistance and is generally resistant to cisplatin and other chemotherapy drugs. Recent studies have indicated that high glycolytic levels may be associated with chemotherapy resistance of cholangiocarcinoma cells and that reprogramming the metabolic model may reverse cisplatin chemotherapy resistance in cholangiocarcinoma. Dichloroacetate (DCA) is a specific inhibitor of PDK, which can promote mitochondrial aerobic oxidation process by activating PDH. In the past few years, there have been an increasing number of studies supporting the action of DCA against cancer, which also provided evidence for targeting metabolism to enhance the efficacy of cholangiocarcinoma chemotherapy, but the specific mechanism still needs to be explored. In this study, we demonstrated that DCA changed the metabolic model from glycolysis to aerobic oxidation in cholangiocarcinoma cells under cisplatin 2 This is a provisional file, not the final typeset article stress. The metabolic reprogramming led to mitochondrial redox dysfunction and increased mitochondrial reactive oxygen species (mtROS) levels. On the one hand, upregulated ROS as a retrograde signal promoted cell cycle arrest and increased the expression of antioxidant genes; on the other hand, such high levels of mtROS activated the cell protection machinery of cholangiocarcinoma cells, such as autophagy. Inhibition of autophagy further increased the synergistic effect of DCA and cisplatin. Collectively, we provide evidence that DCA increased cisplatin sensitivity in cholangiocarcinoma cells via increasing the mitochondria oxidative stress and cell growth inhibition. Synergistic effects of DCA and CQ were observed in cholangiocarcinoma cells, which further increased the cisplatin sensitivity via both metabolic reprogramming and inhibiton of the stress reponse autophagy.